Gender and Climate Smart Agricultural Practices: Evidence from Bangladesh - Quisumbing, Agnes R.; Kovarik, Chiara; Bernier, Quinn (2015)
Presentation by Agnes Quisumbing, Chiara Kovarik, and Quinn Bernier from the International Food Policy Research Institute (IFPRI)